Pathophysiology of Spinal Cord Injury (SCI) (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Spinal cord injury (SCI) leads to paralysis, sensory, and autonomic nervous system dysfunctions. However, the pathophysiology of SCI is complex, and not limited to the nervous system. Indeed, several other organs and tissue are also affected by the injury, directly or not, acutely or chronically, which induces numerous health complications. Although a lot of research has been performed to repair motor and sensory functions, SCI-induced health issues are less studied, although they represent a major concern among patients. There is a gap of knowledge in pre-clinical models studying these SCI-induced health complications that limits translational applications in humans. This reprint describes several aspects of the pathophysiology of spinal cord injuries. This includes, but is not limited to, the impact of SCI on cardiovascular and respiratory functions, bladder and bowel function, autonomic dysreflexia, liver pathology, metabolic syndrome, bones and muscles loss, and cognitive functions.